Excited‐State Intramolecular Charge‐Transfer Dynamics in 4‐Dimethylamino‐4′‐cyanodiphenylacetylene: An Ultrafast Raman Loss Spectroscopic Perspective - Barak, Arvind; Dhiman, Nishant; Sturm, Floriane; Rauch, Florian; Lakshmanna, Yapamanu Adithya; Findlay, Karen S.; Beeby, Andrew; Marder, Todd B.; Umapathy, Siva (ChemPhotoChem, 2022)
The D-π-A compound 4-dimethylamino-4′-cyanodiphenylacetylene (DACN-DPA) exhibits intramolecular charge transfer (ICT) upon photoexcitation. Ultrafast Raman Loss Spectroscopy (URLS) measurements show distinct spectral and temporal dynamics of C≡C and C=C vibrational modes in MeCN and n-hexane, revealing that ICT is strongly coupled to the structural dynamics. Photo-initiated intramolecular charge transfer (ICT) processes play a pivotal role in the excited state reaction dynamics in donor-bridge-acceptor systems. The efficacy of such a process can be improved by modifying the extent of π-conjugation, relative orientation/twists of the donor/acceptor entities and polarity of the environment. Herein, 4-dimethylamino-4′-cyanodiphenylacetylene (DACN-DPA), a typical donor-π-bridge-acceptor system, was chosen to unravel the role of various internal coordinates that govern the extent of photo-initiated ICT dynamics. Transient absorption (TA) spectra of DACN-DPA in n-hexane exhibit a lifetime of >2 ns indicating the formation of a triplet state while, in acetonitrile, a short time-constant of ∼2 ps indicates the formation of charge transferred species. Ultrafast Raman loss spectroscopy (URLS) measurements show distinct temporal and spectral dynamics of Raman bands associated with C≡C and C=C stretching vibrations. The appearance of a new band at ∼1492 cm−1 in acetonitrile clearly indicates structural modification during the ultrafast ICT process. Furthermore, these observations are supported by TD-DFT computations.
EPrint Processing Status: Full text deposited in DRO